Prospective study of pigmented lesions managed by shave excision with no deep margin transection of melanomas. (17th May 2020) - Shao, Emily; Blake, Tony; Po-Chao, Frank; Pool, Louis; Carew, Benjamin; Yong‐gee, Simon; Wheller, Laura; De'Ambrosis, Brian; Muir, James
Abstract: Shave excision is a simple and cost‐effective technique for the removal of suitable skin lesions. We performed a prospective study over six months, collecting data from pigmented lesions that were treated with shave excision by dermatologists. Only shave excisions with the intent to remove the lesion in toto were included. A total of 349 lesions were included in this study, 50 (14%) of these were melanomas and no melanoma diagnosed had deep margin involvement, while 13 (26%) had lateral margin involvement.